MAPS, Malaysia Company - Maulana, Muhammad Iqbal; Kee, Daisy Mui Hung; Binti Rosli, Intan Natasha; Binti Borhan, Nadia; Binti Azir, Noorazira; Huey, Wong Ming (AIBPM Publisher, 2019)
MAPS Perak (Movie Animation Park Studio of Perak) is a theme park in Ipoh, Perak, Malaysia which was created from a joint venture between Perak Corporation Berhad and the Sanderson Group. It was originally planned to be opened in 2015, but the opening date was delayed to 26 June 2017. The theme park is the first fully animation-based theme park in Asia which contains attractions based on animations such as DreamWorks Animation and The Smurfs and was built at the cost of RM520 million. It houses both international and homegrown (Malaysian) Intellectual Properties including DreamWorks characters, The Smurfs and BoBoiBoy and have more than 40 attractions in six themed zones. This is the first theme park in Malaysia that portray or using local animation as the theme of the amusement park. The purpose of the project is to discuss the problems faced by the Movies Animation Park Studios (MAPS) Perak from different perspectives such as financially, marketing and politics. This project also aims to suggest a solution to Movies Animation Park Studios (MAPS) Perak regarding these problems. Knowing and understanding the wider what is the cause of the company facing these problems. And also gives pro and cons about each decision make by this company when the company facing the problem. The methodology that we will use in this research is the primary method and secondary method. The primary method is when the data we collected directly from the owner or the owns of the data. This is different from the secondary method, which is the secondary method we get the data from the other resources which are carried out by other people. An example primary method by interviewing the manager and the staff of MAPS to make some surveys for our research. We do this interview by phone. Example of the secondary method is by doing research by collecting the data from their website and the other information. For our company cases, the problems with MAPS, Perak Malaysia are their awareness is low which means their marketing is not strategic in terms of costs and do not give high impact to the sales. Moreover, the price ticket that they offer for a customer is very expensive and did not worth the money and achieve customer expectations. The games in the theme park are not satisfying with. So the price is not a great deal to attract the outsider. Besides, this company also have faced the political issue which is Malaysia’s government has advice MAPS to close down this theme park because they have too much liability and they couldn’t afford it.